Isolation and Biological Activity Assessment of Bioactive Compounds from Hygrophila salicifolia (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Hygrophila salicifolia, a medicinal plant with historical therapeutic applications, was investigated for its phytochemical, pharmacognostic, and pharmacological properties. This study isolated and characterized bioactive compounds, particularly flavonoids, from its methanolic extract, using advanced chromatographic and spectroscopic methods. The extract demonstrated potent antioxidant and anti-urolithiatic activity in vitro and in vivo. It significantly reduced urinary calcium, oxalate, and phosphate levels while increasing magnesium excretion in an ethylene glycol-induced urolithiasis model in rats. Histopathological analysis revealed reduced renal damage and crystal deposition in treated groups. The flavonoid glycoside, identified as isoquercitrin, exhibited promising therapeutic potential, substantiating the plant's traditional medicinal use. This research underscores Hygrophila salicifolia's potential as a natural source for developing treatments for urolithiasis and other oxidative stress-related conditions.